Effects of the economic recession on suicide mortality in Brazil: interrupted time series analysis - Daniela Cristina Moreira Marculino de Figueiredo; Pablo Sanchéz-Villegas; Alexandre Medeiros de Figueiredo; Ronei Marcos de Moraes; Antonio Daponte-Codina; Ricardo Schmidt Filho; Rodrigo Pinheiro de Toledo Vianna (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze trends in suicide rates in Brazil in the period before and after the start of the economic recession. Methods: interrupted time series research using national suicide data recorded in the period between 2012 and 2017 with socioeconomic subgroups analyses. Quasi-Poisson regression model was employed to analyze trends in seasonally adjusted data. Results: there was an abrupt increase in the risk of suicide after economic recession in the population with less education (12.5%; RR = 1.125; 95%CI: 1.027; 1.232) and in the South Region (17.7%; 1.044; 1.328). After an abrupt reduction, there was a progressive increase in risk for the black and brown population and for those with higher education. In most other population strata, there was a progressive increase in the risk of suicide. Conclusions: the Brazilian economic recession caused different effects on suicide rates, considering social strata, which requires health strategies and policies that are sensitive to the most vulnerable populations.